Spatial Statistical Analysis of the relation in between population density and Human Modification of terrestrial lands at Tabia level in the Tigray Region of Ethiopia - Islam, Zubairul; Asefa , Abrha; Berhe, Asefa Tesfay (Acta Geographica Debrecina Landscape & Environment series, 2020)
In this study first spatial pattern of the level of human modification of terrestrial lands and second its relation with population density was studied at Taiba level in the Tigray regional state of Ethiopia. For the level of human modification of terrestrial lands global Human Modification dataset (gHM) was used and for population density Gridded Population of the World, Version 4 (GPWv4.11) dataset was used. Both the data set were preprocessed before geostatistical analysis. To measure the distribution pattern Global Moran’s I statistics, Cluster and Outlier Analysis (Anselin Local Morans I) statistics was used. To measure the relation between population density and human modification of terrestrial lands geographically weighted regression was used. In the case of first objective the resulting z-score of 50.50, confirm the tabias with high Human Modification of terrestrial lands are highly clustered. In case of second objective the results shows 214 Tabias containing high value and are surrounded by Tabias with high values (HH), 10 Tabias containing high value and is surrounded by Tabias with low values (HL). The relation between population density and human modification of terrestrial lands was found positive with R2= 0.506. This research will help the government and planners for proactive spatial planning to maintain biodiversity and ecosystem function before important environmental values are lost in tabias containing high value and is surrounded by Tabias with high values.